A scalable, high-throughput optomotor response pipeline for quantitative analysis of vision using infinity-pools - Suzuki, Risa; Kalšan, Damjan; Bhatti, Norin; Pierotti, Saul; Hofmann, Gero; Birney, Ewan; Thumberger, Thomas; Wittbrodt, Joachim (bioRxiv beta, 2026)
The optomotor response (OMR) provides a robust readout assay for evaluating visually guided locomotion and has been widely applied to various animal models. We present a scalable, high-throughput OMR platform with tuneable and moving stripe patterns simultaneously projected to the side of 50 petri dishes. The setup is optimized for hatchling-stage medaka (Oryzias latipes and Oryzias sakaizumii) and larval stage zebrafish (Danio rerio) and integrates custom software for automated generation of visual stimuli and specimen detection, enabling precise and automated quantification of optomotor behaviour across thousands of individuals. Using this platform, we systematically assess the visual performance of zebrafish and five medaka strains. By varying stripe width, direction, speed, contrast, and colour, we address spatial resolution, contrast, and colour sensitivity. Albino mutant medaka exhibited the highest sensitivity, responding at lower stripe widths and across a broader range of contrasts and chromatic conditions. Interestingly, some Cab and HO5 hatchlings displayed uni-directional response, revealing strain-specific visuomotor differences. Our platform enables reliable detection of OMR behaviour already at hatching and supports robust analysis of visuomotor function. The modular design, automated detection, analysis pipeline, and capacity for large sample numbers make it a powerful tool for comparative vision research, high-throughput genetic screening, and systematic behavioural profiling.